To Come to the Land : Immigration and Settlement in 16th-Century Eretz-Israel. - David, Abraham (Judaic Studies Series, 1999)
Abraham David here focuses on the Spanish and Portuguese Jews who fled the Iberian Peninsula during the 16th century, tracing the beginnings of Sephardic influence in the land of Israel. After the Ottoman Turks conquered Syria, Palestine, and Egypt in 1516, the Ottoman regime, unlike their Mamluk predecessors, encouraged economic development and settlement throughout the region. This openness to immigration offered a solution to the crisis Iberian Jews were undergoing as a result of their expulsion from Spain and the forced conversions in Portugal. Within a few years of the Ottoman conquest, Je.